2006
DOI: 10.1029/2005jd006490
|View full text |Cite
|
Sign up to set email alerts
|

Deep convective influence on the Asian summer monsoon anticyclone and associated tracer variability observed with Atmospheric Infrared Sounder (AIRS)

Abstract: [1] The Asian summer monsoon anticyclone is linked to climatological deep convection over Southeast Asia, and the coupling of circulation and convection strongly influences constituent behavior in the upper troposphere -lower stratosphere (UTLS). This work explores the variability of the Asian monsoon circulation and trace constituents linked to transient deep convection, on the basis of dynamical fields and outgoing longwave radiation (OLR) data, plus water vapor and ozone retrievals from the Atmospheric Infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
471
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 383 publications
(517 citation statements)
references
References 40 publications
45
471
1
Order By: Relevance
“…As shown Figure 1 (top), a prominent water vapor maximum of 6.5 ppmv is found at 100 hPa above Asia. This anomaly is well above the precision threshold of MLS (15% according to Livesey et al [2005]) and agrees with the persistent seasonal feature observed by AIRS and HALOE [Gettelman et al, 2002b;Randel and Park, 2006]. A secondary maximum of about 5.5 ppmv corresponding to the American monsoon is observed over North Mexico and the East coast of Pacific Ocean.…”
Section: Observations Of the Asian Monsoon Regionsupporting
confidence: 70%
See 1 more Smart Citation
“…As shown Figure 1 (top), a prominent water vapor maximum of 6.5 ppmv is found at 100 hPa above Asia. This anomaly is well above the precision threshold of MLS (15% according to Livesey et al [2005]) and agrees with the persistent seasonal feature observed by AIRS and HALOE [Gettelman et al, 2002b;Randel and Park, 2006]. A secondary maximum of about 5.5 ppmv corresponding to the American monsoon is observed over North Mexico and the East coast of Pacific Ocean.…”
Section: Observations Of the Asian Monsoon Regionsupporting
confidence: 70%
“…Randel and Park [2006] show coherent fluctuations in deep convection and water vapor inside the Asian monsoon anticyclone between the potential temperature levels 340-360 K and moistening convective events are identified in the extratropics over Asia [Dessler and Sherwood, 2004] and over the Tibetan Plateau [Fu et al, 2006]. However, the water vapor maximum at 100 hPa does not spatially or temporally correspond to the maximum of convective activity [Park et al, 2007], suggesting an important role of the horizontal transport.…”
Section: Introductionmentioning
confidence: 99%
“…The UTLS anticyclone is a seasonal feature, beginning in June and ending in September. The evolution over the season is characterized by large variability in the extent, strength, and location of the anticyclone [Randel and Park, 2006]. Oscillations with periods of 10-20 and 30-60 days were found by Annamalai and Slingo [2001], and they concluded that these are driven by variations in the monsoon convection.…”
Section: Introductionmentioning
confidence: 99%
“…The strong circulation of the anticyclone acts to isolate air, and because this isolated air is tied to the outflow of deep convection, the anticyclone often has a distinct chemical signature [Dethof et al, 1999;Randel and Park, 2006;Park et al, 2007Park et al, , 2008Baker et al, 2011]. The UTLS anticyclone is a seasonal feature, beginning in June and ending in September.…”
Section: Introductionmentioning
confidence: 99%
“…During northern summer, most of the transport is shifted towards India where the steering of parcel trajectories by the monsoon anticyclone is such that those parcels trapped in the anticyclone at the tropopause avoid the coldest point and enter the stratosphere with more than 4 ppmv of water vapour. This is manifested in a 'wet fountain', observed from EOS MLS on the NASA Aura platform (Randel and Park, 2006) and reproduced by Lagrangian models (M. Bonazzola and P. James 2007, personal communication). The representation of clouds is the weak point of large-scale Lagrangian calculations, which thus cannot take account of the role of overshooting convection which can inject water several kilometres above the tropopause (Dessler et al, 2006;Chaboureau et al, 2007;Grosvenor et al, 2007;Pommereau et al, 2007).…”
Section: Transportmentioning
confidence: 99%